Virtual Classroom Tools in Music Education - Tokatli, Muhammed Omer; Can, A. Aylin; Yungul, Okan (ISRES Publishing, 2024)
Education is also continued with distance education, which is an alternative model with the support of technology. The formation of student and teacher environment in distance education depends on the virtual classroom. Virtual classroom is an educational environment where individuals in different places come together simultaneously through internet infrastructure and computer. Virtual classroom is applied in many disciplines of the education system. The high motivation of the students during the lesson in the virtual classroom and the permanence of learning depend on the virtual classroom tools used during the lesson. However, it is not known under which titles virtual classroom tools are applied in music education, which is a part of the education system. Based on this problem, it was aimed to reveal the dimensions in which virtual classroom tools are applied in music education. Based on the data obtained, it was determined that there are tools specific to music education as well as tools used in general education. In the literature review, it was determined that the tools used in music education are grouped under five headings: recording technology, note writing, sound organisers, in-class activities and artificial intelligence. According to the results of the research, the importance of music teachers' use of educational technologies and the positive effect of virtual classroom tools on students in music lessons have emerged. The necessity of providing in-service training for teachers on the utilisation of virtual classroom tools in the curriculum of music education was emphasised, as was the role of technology in music education in the contemporary context.